Anisotropic frost heaving coefficient of saturated permafrost considering moisture migration process based on standards - Hui GE; Chunxiang GUO; Lei ZHANG (Shuiwen dizhi gongcheng dizhi, 2025)
Frost heave in positive permafrost is a critical factor leading to frost damage of engineering in the cold region. The frost heave process results from the dynamic interaction of hydro-thermal forces. In an open system, factors such as temperature, temperature gradient, water content, and water supply intensity significantly influence the deformation of positive permafrost frost heave. Frost heave in permafrost is the combined effect of vertical segregated frost heave due to moisture migration and in-situ frost heave, and its mechanical characteristics of frost heave are anisotropic. This study, referencing the standard process of ice content variation in soils during freezing, takes into account factors such as Poisson’s ratio, groundwater table depth, and cooling rate. the calculation methods for the frost heave coefficients in the horizontal and vertical directions during the freezing process of positive permafrost were derived. By comparing the frost heave coefficients of silt and silty clay, the results show good agreement with experimental data. In the case study, the vertical frost heave coefficient of silt ranges from −1.37×10−3 to −7.67×10−3, and the horizontal frost heave coefficient ranges from −0.81×10−3 to −4.85×10−3 within the temperature range of −0.2 °C to −3.0 °C and a depth range of 0.2 m to 1.0 m. The percentage difference ranges from 10.4% to 77.7%, indicating the necessity of considering the anisotropy resulting from segregated frost heave. The calculation methods for horizontal and vertical frost heave coefficients in this study can provide valuable information for frost damage of engineering in the cold region.